Acute respiratory symptoms associated with short term fluctuations in ambient pollutants among schoolchildren in Durban, South Africa. (February 2018) - Mentz, Graciela; Robins, Thomas G.; Batterman, Stuart; Naidoo, Rajen N.
Abstract: Ambient air pollution has been associated with adverse respiratory outcomes, especially among children with asthma. This study reports on associations between daily ambient air pollutant concentrations and the respiratory symptoms of schoolchildren living in Durban, South Africa. This city is Africa's busiest port and a key hub for imported crude oil and exported refined petroleum and petrochemical products, and it experiences a mixture of air pollutants that reflects emissions from industry, traffic and biomass burning. Children in four communities in the highly industrialized southern portion of the city were compared to children of similar socio-economic profiles living in the north of the city. One school was selected in each community. A total of 423 children were recruited. Symptom logs were completed every 1.5–2 h over 3-week period in each of four seasons. Ambient concentrations of NO2, NO, SO2, CO, O3, PM2.5 and PM10 were measured throughout the study. Generalized estimating equation (GEE) models were used to estimate odds ratios (ORs) and assess lag effects (1–5 days) using single pollutant (single lags or distributed lags) models. Concentrations of SO2 and NOx were markedly higher in the south, while PM10 did not vary. Significant increase in the odds ratios of cough were identified for the various lags analyzed. The OR of symptoms was further increased among those living in the south compared to the north. In conclusion, in this analysis of over 70, 000 observations, we provide further evidence that exposure to PM10, SO2, NO2 and NO is associated with significantly increased occurrence of respiratory symptoms among children. This was evident for cough, shortness of breath, and chest tightness, across the four pollutants and for different lags of exposure. This is the first study describing these changes in sub-Saharan Africa. Graphical abstract: Image 1 Highlights: The first repeated measures study conducted in sub-Saharan Africa. Multiple ambient exposures across all seasons assessed with over 70 000 observations. New findings for context with higher industrial pollution and different vehicle types. An interquartile range pollutant increase was associated with increased symptom risk. Residence location modified the pollutant-related ORs for symptoms. Abstract : Short term exposure to ambient pollutants in a population based sample of asthmatic and non-asthmatic schoolchildren in South Africa, is associated with increased respiratory symptom risk.